THEORETICAL BASES OF MANAGEMENT OF ADAPTATION OF INNOVATIVE PROCESSES AT THE ENTERPRISE OF MECHANICAL ENGINEERING - M. Shtrikunova; D. Pelikhov; M. Eremenko (Вестник университета, 2016)
Conceptual bases of management of adaptation of innovative processes at the enterprises of mechanical engineering which feature is consideration of management of adaptation of innovative processes in as counter process of adaptation of innovative solutions and processes to conditions of activity of the enterprise, on the one hand, and the adaptation of the enterprise to various changes with use of innovations, with another are defined. This approach allows to improve methods of management of innovative processes by continuous fine tuning under changes of external influences and change of the internal environment.